Basics in Endoscopic Ultrasound Part 1: Diagnostic Indications and Tissue Sampling - Serrani, Marta; Calvanese, Claudio; Lisotti, Andrea; Caletti, Giancarlo; Abenavoli, Ludovico; Fusaroli, Pietro (Reviews on Recent Clinical Trials, 2018)
Background: Endoscopic Ultrasound has been used in the clinical arena for almost 35 years and it is now well-integrated in everyday hospital practice. Method: We conducted a systematic review of the available English-language articles. Objective: The purpose of this review is to summarize all the relevant indications to endoscopic ultrasound and analyze its relevant data in terms of accuracy and clinical outcomes. Results: More than 5000 scientific papers published in the literature have demonstrated its high accuracy for the diagnosis and staging of a variety of benign and malignant conditions. Staging indications include gastroesophageal and rectal cancers. Diagnostic, staging and therapeutic indications include diseases of the pancreaticobiliary area. Finally, differential diagnosis of submucosal tumors represents another important indication to this technique.
Keywords: Endoscopic Ultrasound